Does AI Dependency Hinder or Enhance Critical Thinking? Examining the Role of Self-Regulation - Firman Alamsyah Ario Buntaran; Dhani Irmawan; Ahmad Sabir (Kuras Institute, 2026)
The reliance on artificial intelligence (AI) in higher education raises questions about its impact on students' critical thinking. This study aims to examine the mediating role of self-regulation (SR) in the relationship between AI dependency (AID) and critical thinking (CTh) among university students with a total of 112 respondents, 35 male students and 77 female students, with an average age of 24 years old. Correlation analysis revealed no direct relationship between AI dependency (AID) and critical thinking (CTh), but AID showed a significant correlation with self-regulation (SR), and SR was strongly correlated with critical thinking (CTh). Mediation analysis demonstrated that SR partially mediating the relationship between AID and CTh, indicating that the impact of AI dependency on critical thinking depends on its influence on self-regulation. These findings align with prior research highlighting the critical role of self-regulation in technology-based learning. Further research is recommended to explore in more depth the role of self-regulation as a variable that may influence the relationship between AI use and potential dependency.